Evaluation of a prescription support-tool for chronic management of oral antithrombotic combinations in adults using clinical vignettes: protocol of a randomised controlled trial. Issue 6 (9th June 2019) - Zerah, Lorene; Bonnet-Zamponi, Dominique; Frappé, Paul; Hauguel-Moreau, Marie; De Rycke, Yann; Magnier, Anne-Marie; Pautas, Eric; Charles, Pierre; Collet, Jean-Philippe; Dechartres, Agnes; Tubach, Florence
Abstract : Introduction: Improving the appropriateness of prescriptions of oral antithrombotic (AT) drugs, especially AT combinations, is crucial because these drugs are implicated in bleeding events. We developed a prescription support-tool synthesising guidelines on chronic management of oral AT combinations. Our main objective is to assess the impact of this tool on improving the prescription of oral ATs to comply with guidelines. Methods and analysis: A randomised controlled trial will be conducted among French general practitioners and cardiologists involved in outpatient settings. Physicians will be invited to participate to an online survey by email via physician associations, social networks or word of mouth. They will be randomised to two arms: the experimental arm (access to the prescription support-tool) or the control arm (no prescription support-tool). Then, all participants will be presented three different clinical vignettes illustrating outpatient clinical situations and will be asked to propose prescriptions for each vignette (number of ATs, type, dosage and duration). A computer-generated randomisation scheme implemented in the online survey will be used to allocate physicians to the experimental or control arm and then stratified by medical specialty. The primary outcome will be fully appropriate prescription of oral ATs ie, that comply with the guidelines in terms of number of drugs, drug class, dosage and duration. To demonstrate a 5% increase in this proportion, we will need to include a minimum of 230 physicians per arm. A logistic mixed model with a clinical vignette-effect and a physician-effect nested in the arm of the study will be used. Ethics and dissemination: The Institutional Review Board of Inserm (IRB00003888) approved our research project (no. 18–492). If the prescription support-tool improves the prescription of oral ATs, we will create an interactive web tool and will assess its impact in terms of clinical outcomes in real-life. Trial registration number: NCT03630874 ; Pre-results.